Menghalau Domestifikasi dan Feodalisme: Daya Subjektivitas NH. Dini dalam Novel "Jalan Bandungan" - Afdholy, Nadya; Tjahjono, Tengsoe (Puitika, 2020)
The journey of Nh. Dini in fighting symbolicism can be examined through the relationship between Nh. Dini as a writer and her work sentitled Jalan Bandungan. Actions again symbolicism are categorized as effort stoliberate the subject to achieve the autonom ous. This study aim storeveal the subjectivity of Nh. Dini as the author of the novel Jalan Bandungan by utilizing the concep to subjectivity that was conceived by SlavojÅ½iÅ¾ek. This research uses a qualitative method and Todorov's point of view analysis approach. The object o fthis research is the novel by Nh. Dini entitled Jalan Bandungan. This study uses data collection techniques with comprehensive reading anduses data analysis techniques by recording. The results of this study indicate that the subjectivity of Nh. Dini in writing the novel Jalan Bandungan is a radical actagainst the symbolic prisons of domestification and feudalism. The entireprocess of writing the novel Jalan Bandungan shows radicalactions Nh. Dini. The action gave rise to symbolic changes that surrounded Nh. Dini and simultane ously attract subjectivity Nh. Dini to return to the symbolic. Keywords: Jalan Bandungan, Nh. Dini, subjectivity, symbolic, Å½iÅ¾ekian.